1983
DOI: 10.1159/000149348
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Transforming Epstein-Barr Virus in Oropharyngeal Secretions of Rheumatoid Arthritis Patients

Abstract: To determine if rheumatoid arthritis (RA) patients have an increased frequency of Epstein-Barr virus (EBV) shedding into saliva, throat washings were collected from 59 patients with RA and 64 healthy adult controls. EBV in filtered samples was detected by transformation of human umbilical cord lymphocytes. EBV was detected in 27% (16/59) of throat washings of RA patients compared to 11% (7/64) of control samples. This difference is significant (p < 0.05). RA patients on steroids had a frequency of positivity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…They found that patients on treatment with corticosteroids were more frequently positive than those who were not, but this was the same for the control patients as for the RA patients. Aitcheson et al [1] describe similar findings. Yao et al [157], using a technique for detection of infectious virus that was apparently more sensitive, found a somewhat higher frequency of positives from the RA patients than from their controls.…”
Section: E B V Virion or Genome Expression In Ramentioning
confidence: 66%
“…They found that patients on treatment with corticosteroids were more frequently positive than those who were not, but this was the same for the control patients as for the RA patients. Aitcheson et al [1] describe similar findings. Yao et al [157], using a technique for detection of infectious virus that was apparently more sensitive, found a somewhat higher frequency of positives from the RA patients than from their controls.…”
Section: E B V Virion or Genome Expression In Ramentioning
confidence: 66%
“…In these conditions, T-cell function is believed to be compromised. In SS patients, T-cell function and natural killer cells have also been reported to be abnormal (Diaz-Jouanen et al 1981;Aitcheson et al 1983;Rickinson et al 1981;Miyasaka et al 1980), suggesting a similar pathophysiology. Although the mechanism of increased levels of EBV genomes in SS patients is not clearly understood, T-cell abnormalities may enable EBV to mfiltrate the B-cells of SS patients' lacrimal glands (Pepose et al 1990).…”
Section: Discussionmentioning
confidence: 99%
“…In the studies giving percentage of EBV excretion in normal individuals [1,3,4,8,9,17,19,20], the percentage range from 0% to 27%. However, the numbers of tested individuals are generally low.…”
Section: Olt Patientsmentioning
confidence: 99%